Design of capacitive electrostatic probes for online measurement of surface charge on ±320 kV tri‐post insulators - Jiayi Liu; Xiaoqing Xie; Feng Wang; She Chen; Qiuqin Sun; Lipeng Zhong; Xianhao Fan; Fangwei Liang (IET Generation, Transmission & Distribution, 2024)
Abstract Compared to offline measurement (interrupting the applied voltage before measurement), online measurement of surface charge on gas‐insulated transmission line (GIL) insulators effectively avoids the impact of spontaneous dissipation of charges. Thus, the accuracy of results can be improved. In this article, a measurement model of capacitive electrostatic probes for surface charges on ±320 kV GIL tri‐post insulator is established. The geometry of probes is optimized. The feasibility of online measurement of surface charges is analyzed. Results indicate that the surface leakage distance of induced charges is positively related to the length. Furthermore, as the diameter of probes increases, the maximum electric field on the sensitive electrode surface rises, while the radius of the sensitive electrode has the opposite effect. Hence, the diameter of the probe is 6 mm. The length and radius of sensitive electrodes are 50 mm and 1.2 mm, respectively. For online measurement of surface charges on ±320 kV tri‐post insulators, the induced potential distribution of the probe is consistent with surface charges. Therefore, the capacitive electrostatic probe in the embedded electrode is appropriate for the online measurement of surface charges on tri‐post insulators. It provides a reference for avoiding flashover triggered by surface charge accumulation on DC GIL insulators.